Governance für eine moderne Industriepolitik: Das Beispiel des saarländischen Transformationsfonds - Jakob von Weizsäcker (Wirtschaftsdienst, 2025)
Die Transformation im Saarland ist durch eine energieintensive Wirtschaftsstruktur und hohe Branchenkonzentration, insbesondere Stahl und Automotive, besonders herausfordernd. Den Erfolg des Transformationsfonds, der angesichts einer außergewöhnlichen Notsituation im Sinne der Schuldenbremse eingerichtet wurde, sollen fünf Governance-Elemente inklusive einer Verantwortungspartnerschaft sichern: (1) strengere Kontrollrechte des Landtags als im Kernhaushalt; (2) eine klare Abgrenzung der Transformation von anderen Politikfeldern; (3) eine Anhebung der Investitionsquote im Kernhaushalt zur Finanzierung zusätzlicher Investitionen; (4) die Ansiedlung der Geschäftsstelle des Fonds im Finanzministerium als zusätzlicher Ansprechpartner für die Risikoeinschätzung des Projektportfolios und (5) eine konstruktivkritische Begleitung durch einen unabhängigen Beirat. – – The transformation in Saarland is particularly challenging due to an energy-intensive economic structure and high industry concentration, especially in steel and automotive. This article explores a number of governance features of the Saarland Transformation Fund as an example of governance for industrial policy. The starting point was a broad-based consensus across the political spectrum and between the social partners to set up the Fund and to keep it running. The necessary level of trust is reinforced by five governance features: First, tight supervisory powers of the regional parliament. Second, a clear-cut mandate of the Transformation Fund to spend exclusively in the areas of industrial policy, infrastructure and innovation (the "Three Is") in order to avoid mission creep. Third, a firm political commitment to increase investment spending in the core budget, thus preventing indirect leakage which might otherwise have occurred by means of moving investment expenditures from the core budget to the Transformation Fund. Fourth, structured vetting of spending proposals by the Fund's secretariat at the Ministry of Finance before being presented to the board of the Fund. Fifth, an independent advisory council to the Fund bringing together outstanding and outspoken experts that offer a wealth of different perspectives.
Keywords: D72; L52; O25; 330